On a class of dual Rickart modules - Tribak, R. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.5 Let R be a ring and let Ω_R be the set of maximal right ideals of R. An R-module M is called an sd-Rickart module if for every nonzero endomorphism f of M, f is a fully invariant direct summand of M. We obtain a characterization for an arbitrary direct sum of sd-Rickart modules to be sd-Rickart. We also obtain a decomposition of an sd-Rickart R-module M, provided R is a commutative noetherian ring and Ass(M) Ω_R is a finite set. In addition, we introduce and study a generalization of sd-Rickart modules.